Scaffold nanoestruturado utilizando-se celulose bacteriana/fosfatos de cálcio para regeneração óssea - Daltro, Paula Braga [UNESP] (2015)
The production of a bacterial cellulose scaffold / calcium phosphates (CB / PCa) obtained from standard simulated body fluid (SBF) and modified SBFs were stabilished by Aparecida (2009) were incorporated to optimize calcium phosphate phase formation in order to enhance bone regeneration. Samples from bacterial cellulose have been coated with calcium phosphate per SBF established by Ali et al. 2009 and six other SBF conditions changed. Two differente bacterial cellulose were compared, the membrane product of dried hydrogel and commonly used in reaserch was after dried incorporated with the SBFs and the hydrogel in natura incorporated with the PCa was then dried and processed into hydrogel powder, both produced under the same coating conditions. The phase formation of HA and other calcium phosphates were visualized in all samples. In this work, the influence of the standard SBF and modified SBFs (1, 2, 3, 4, 5 and 6) were analyzed chosen in the formation of calcium phosphate phases on the surface of the bacterial cellulose membrane. It was also studied the influence of this biofilm / CaP on cell pre-osteoblast cells viability. The characterization of the samples was done by scanning electron microscopy (SEM) X-ray diffraction - XRD, spectroscopy in the infrared Fourier transform (FTIR) and thermal analysis (TGA, DSC, DTG). The biological testing character was done on both conditions by the MTT reduction method. Cytotoxicity was not identified in any of the samples tested.